Clinical and epidemiological characteristics of imported intestinal infections in children - E. Yu. Pylaeva; N. N. Zverevа; А. А. Erovichenkov; S. K. Pylaeva; E. A. Artamonova; N. Yu. Pshenichnaya; A. M. Demkina; O. N. Solodovnikova; Yu. N. Khlypovka; A. Yu. Dyagileva; A. Kh. Nurpeysova; A. U. Berestovskaia; et al. (Детские инфекции (Москва))
Since the beginning of the 21st century, the number of international trips has been increasing in the world. Outbound and domestic tourism is expanding in Russia. During a trip, there are various types of health risks for the traveler, especially for children. These risks include infectious diseases, among which in children intestinal infections come first. That is why this research is important for studying the epidemiology and clinical processes of intestinal infections in childhood in patients returning from travel. The goal is to analyze the clinical and epidemiological characteristics of imported intestinal infections in children who traveled to other countries and in children who returned from Russian regions. Materials and methods. A single-center prospective study using questionnaires and clinical observation was conducted from June to September 2022 in the children's infectious diseases hospital of the Moscow Multidisciplinary Clinical Center «Kommunarka» (MMCC «Kommunarka»). An analysis of the data of 128 travelers who fell ill during or after travel and were admitted to the MMCC «Kommunarka» was carried out. 2 groups were identified — those who traveled to the regions of Russia or other countries. The clinical and epidemiological features of children's disease cases and their vaccination status were analyzed. Results. The children's ages ranged from 1 month to 17 years, and the gender distribution was even. Among the regions of departure, the Krasnodar Territory and Mediterranean coast of Turkey were the most common. There were no differences in travel duration, with a median of 10 days. In the group of people who traveled across Russia, the leading purpose was to visit friends and relatives, while tourists stayed mainly in the private sector. In the case of traveling abroad, the prevailing purpose was tourism, with equal proportions staying in a hotel or private sector. Imported intestinal infections most often occurred with symptoms of gastroenteritis, were assessed by CDS at 5 points, and rotavirus predominated in the etiological structure.